Introduction to animal science : global, biological, social, and industry perspectives - Damron, W. Stephen (Pearson, 2013)
"Introduction to Animal Science: Global, Biological, Social, and Industry Perspectives, Fifth Edition,features the most comprehensive, up-to-date coverage of the traditional disciplines that are so essential to a solid foundation in Animal Science: nutrition, digestion, feeds, genetics, reproduction, disease, and animal behavior. The text's comprehensive, non-traditional approach introduces the discipline as an ever-changing, integral part of every aspect of human existence. Author W. Stephen Damron not only presents thorough coverage of the major species and their respective concerns, he challenges students to consider the many pressing interests relevant to Animal Science as it influences and is influenced by society today."-- Publisher's website